New genera and species with chloridium-like morphotype in the Chaetosphaeriales and Vermiculariopsiellales - Réblová, M; Nekvindová, J (Studies in mycology, 2023)
In this study, we investigated the morphological and genetic variability of selected species belonging to the genus Chloridium sensu lato, some also referred to as chloridium-like asexual morphs and other undescribed morphologically similar fungi. These species do not conform to the revised generic concept and thus necessitate a re-evaluation in terms of taxonomy and phylogeny. The family Chaetosphaeriaceae (Chaetosphaeriales) encompasses a wide range of asexual morphotypes, and among them, the simplest form is represented by Chloridium sect. Chloridium. The morphological simplicity of the Chloridium morphotype has historically led to the amalgamation of numerous unrelated species, thereby creating a heterogeneous genus. By conducting phylogenetic reconstruction of four DNA loci and examining a set of 71 strains, including all available ex-type and other non-type strains as well as holotypes and other herbarium material, we were able to gain new insights into the relationships between these taxa. Phylogenetic analyses revealed that the studied species are distantly related to Chloridium sensu stricto and can be grouped into two orders in the Sordariomycetes. Within the Chaetosphaeriales, they formed nine well-separated genera in four clades, such as Cacumisporium, Caliciastrum gen. nov., Caligospora gen. nov., Capillisphaeria gen. nov., Curvichaeta, Fusichloridium, Geniculoseta gen. nov., Papillospora gen. nov., and Spicatispora gen. nov. We also established Chloridiopsiella gen. nov. and Chloridiopsis gen. nov. in Vermiculariopsiellales. Four new species and eight new combinations are proposed in these genera. Our study provides a clearer understanding of the genus Chloridium, its relationship to other morphologically similar fungi, and a new taxonomic treatment and molecular phylogeny to facilitate their accurate identification and classification in future research. Taxonomic novelties: New genera: Caliciastrum Réblová, Caligospora Réblová, Capillisphaeria Réblová, Chloridiopsiella Réblová, Chloridiopsis Réblová, Geniculoseta Réblová, Papillospora Réblová, Spicatispora Réblová; New species: Caliciastrum bicolor Réblová, Caligospora pannosa Réblová, Chloridiopsis syzygii Réblová, Gongromerizella silvana Réblová; New combinations: Caligospora dilabens (Réblová & W. Gams) Réblová, Capillisphaeria crustacea (Sacc.) Réblová, Chloridiopsiella preussii (W. Gams & Hol.-Jech.) Réblová, Chloridiopsis constrictospora (Crous et al.) Réblová, Geniculoseta preussii (W. Gams & Hol.-Jech.) Réblová, Papillospora hebetiseta (Réblová & W. Gams) Réblová, Spicatispora carpatica (Hol.-Jech. & Révay) Réblová, Spicatispora fennica (P. Karst.) Réblová; Epitypifications (basionyms): Chaetosphaeria dilabens Réblová & W. Gams, Chloridium cylindrosporum W. Gams & Hol.-Jech. Citation: Réblová M, Nekvindová J (2023). New genera and species with chloridium-like morphotype in the Chaetosphaeriales and Vermiculariopsiellales. Studies in Mycology 106: 199-258. doi: 10.3114/sim.2023.106.04.
Keywords: lignicolous fungi; new taxa; conidiogenesis; multi-locus; phialide; Chaetosphaeria